How Software Quality Mediates the Impact of Intellectual Capital on Commercial Open-Source Software Company Success - Garomssa, Shimels D.; Kannan, Rathimala; Chai, Ian; Riehle, Dirk (IEEE Access, 2022)
The recent surge in the number of commercial open-source software (COSS) companies shows the growing importance of COSS companies in the software industry. As knowledge-based firms, COSS companies’ success depends heavily on the interplay among intangible resources such as human capital, relational capital, structural capital, and software quality. To observe these relationships, we conducted a hypothesis-testing questionnaire-type survey involving 200 software development experts and professionals working at 60 multinational COSS companies. Accordingly, the study unearthed two different but conjoint ways (i.e., direct and indirect) in which intellectual capital impacts COSS company’s success. On the one hand, relational capital one of the intellectual capital components directly affects COSS company’s success. On the other hand, relational and structural capital indirectly affect COSS company success through human capital, which, in turn, is itself mediated by software quality in a sequential mediation model. Therefore, COSS companies may need to prioritize software quality as it is the most critical variable impacting the success of COSS companies.<br
Keywords: Companies; Software quality; Software; Integrated circuits; Knowledge management; Knowledge based systems; Open source software